Grace for Grace : The Debates after Augustine and Pelagius - Hwang, Alexander Y. (Book collections on Project MUSE., 2014)
The contributors to Grace for Grace focus on the debates on grace and free will inspired by Augustine's later teachings on grace and the various reactions to it. In both popular and scholarly literature, the conflict has been traditionally referred to as the "Semi-Pelagian Controversy." For several decades, scholars have distanced themselves from that overly-simplistic and inaccurate portrayal. This book intends to solidify a disparate movement of scholarly thought and offer a secure basis for renewed study of the persons, texts, and events of this critical period in the reception of Augustine in the Early Middle Ages. This volume brings together new perspectives, based on fresh study of a wealth of primary sources, from an international team of scholars to explore the intra- church debates over grace and free will, after Augustine and Pelagius. Contributors to this volume are: Rebecca Harden Weaver (Union Presbyterian Theological Seminary), Eugene Teselle (Vanderbilt University), Roland Teske S.J. (Marquette University), Alexander Y. Hwang (Saint Leo University), Raúl Villegas Marín (University of Barcelona), Jeremy Demulle (Universite Paris-Sorbonne (Paris IV), Tommy Hump- hries (Saint Leo University), Boniface Ramsey (Saint Joseph's Church, NY), Augustine Casiday (Cardiff University), Francis X. Gumerlock (Providence Theological Seminary), Matthew Pereira (Loyola University Marymount), Ralph Mathisen (University of Illinois), Brian J. Matz (Carroll College), and Nestor Kavvadas (University of Tübingen).